Effectiveness of Marketing Communication on the Sales Performance of Nepal Telecom - Kunwar, Abhinaya; Dahal, Gangadhar (Nepalese Journal of Business, 2025)
This study examines the effectiveness of marketing communication on the sales performance of Nepal telecom. Sales performance is the dependent variable. The selected independent variables are advertising, sales promotion, publicity and public relation, sponsorship and direct marketing. The primary source of data is used to assess the opinions of respondents regarding advertising, sales promotion, publicity and public relation, sponsorship, direct marketing and sales performance. The study is based on primary data from 126 respondents. To achieve the purpose of the study, a structured questionnaire is prepared. The correlation and multiple regression models are estimated to test the significance and effectiveness of marketing communication on sales performance of Nepal Telecom. The study showed a positive impact of advertising on sales performance. It indicates that higher the advertising, higher would be the sales performance. Similarly, the study showed a positive impact of sales promotion on sales performance. It indicates that higher the sales promotion, higher would be the sales performance. Likewise, the study also revealed a positive impact of publicity and public relation on sales performance. It indicates that higher the publicity and public relation, higher would be the sales performance. Further, the study observed a positive impact of sponsorship on sales performance. It indicates that higher the number of sponsorship, higher would be the sales performance. In addition, the study observed a positive impact of direct marketing on sales performance. It indicates that adoption of direct marketing strategy leads to increase in sales performance.